Perbedaan kontrol diri siswa dalam penggunaan smartphone ditinjau dari jenis kelamin - Afla Khairani; Indah Sukmawati (Universitas Negeri Padang, 2023)
This study aims to analyze differences in students' self-control in using smartphones in terms of gender. This research uses a quantitative method with a comparative descriptive research type. The population of this study was 969 students at SMAN 4 Payakumbuh with a sample of 287 students. The sample was taken using a stratified random sampling technique. The instrument used was a